An Opportunity for Cognitive Task Analysis in Neonatal Resuscitation - Zehnder, Emily C.; Law, Brenda H. Y.; Schmölzer, Georg M. (Frontiers in Pediatrics, 2019)
Approximately 10% of newborn infants require resuscitative intervention at birth. Ideally, this care is provided by a team of expert healthcare professionals who possess exceptional cognitive, psychomotor, and communication skills. Human errors and deviations from resuscitation protocol are common and may be attributable to excessive cognitive demand experienced by the resuscitation team. Cognitive Task Analysis (CTA) is a group of methods used to assess knowledge, judgments, goals, and decision-making of expert healthcare professionals. These methods may be used during neonatal resuscitation to gain an improved understanding of the approaches used by healthcare professionals. CTA methods have been applied in many medical disciplines including neonatology. CTA has been used to identify information previously confined to the intuition of experts. This information has been used to assess, develop, and improve medical technology, clinical decision support tools, communication structure, and training methods. Knowledge attained through CTA might be applied similarly to neonatal resuscitation, which may, in turn, decrease human errors, and improve patient safety.